Role of acid-treated CNTs in chemical and electrochemical impedance study of dye-sensitised solar cell. (20th February 2018) - Mahalingam, S.; Abdullah, H.; Manap, A.
Abstract: This study aims on the degradation performance of In2 O3 and In2 O3 mixed with acid-treated CNTs (MWCNTS and SWCNTs) for dye-sensitised solar cell (DSSC) application. The thin films were prepared by sol-gel method using spin coating technique annealed at 450 °C. The pristine carbon nanotubes were chemically treated in an acid mixture of H2 SO4 /HNO3 to improve the performance of CNTs addition in In2 O3 -based DSSC. The X-ray diffractometer result proves the thin films possess body-centered cubic phase (JCPDS no. 01-071-2194). The high resolution-transmission electron microscopy analysis shows the internal structures of CNTs before and after acid-treatment process. Meanwhile, the ultraviolet–visible spectrophotometry analysis determines lower energy band gap in the acid-treated CNTs by increasing the open circuit voltage. However, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy analysis revealed acid treatment process in MWCNTs caused more defects that influenced the performance of DSSC. The FTIR peaks confirm the formation of COOH groups at the CNTs after the acid treatment process. Furthermore, the appearance of shoulder like arc at both In 3d5/2 and In 3d3/2 in the XPS peaks in In2 O3 -SWCNTs indicates a good interaction of chemical bonding between In2 O3 and SWCNTs. Besides that, In2 O3 -SWCNTs possesses slower electron recombination rate with longer electron lifetime of 3.03 m s. Although, In2 O3 -MWCNTs exhibits higher short circuit current density ( J sc ) than In2 O3 -SWCNTs the occurrence of defects during acid treatment in MWCNTs caused higher electron recombination rate and decreased the electron lifetime of the cell.